DETERMINAN YANG MEMPENGARUHI STATUS KESEHATAN IBU HAMIL SELAMA PANDEMI COVID-19 - Rubiati Hipni; Hapisah Hapisah; Serilaila Serilaila (MMJ (Mahakam Midwifery Journal), 2021)
Abstract The Corona virus that causes SARS & MERS is known to cause birth complications such as abortion, premature birth, IUGR & maternal death. Vertical transmission from mother to fetus is not known for certain, but the impact of the Covid-19 pandemic on maternal health in Indonesia can occur through disruption of maternal health services and the risk of Covid-19 infection in pregnant women. The purpose of this study was to determine the determinants that affect the health status of pregnant women during the Covid-19 pandemic in the Martapura City Midwife Independent Practice. The research design used is descriptive analytic with a cross sectional approach. The number of samples is 100 pregnant women, using offline and online questionnaires. The analysis used was the Spearman Rank Correlation test. The results showed that there was a significant relationship between age (p 0.001), education (p 0.037), knowledge (p 0.020), Economic Status (p 0.003), frequency of ANC (p 0.045), and history of disease. (p 0.000) with Maternal Health Status because the p-value <0.05. Occupation (p 0.816), Parity (p 0.89), Pregnancy Distance (p 0.288), and Nutritional Status of Pregnant Women (0.891) had a p-value > 0.05 so statistically not related to the Health Status of Pregnant Women. Conclusion age, education, knowledge, economic status, frequency of ANC and disease history can affect the health status of pregnant women. Abstrak Virus Corona penyebab SARS & MERS menyebabkan komplikasi persalinan seperti Aborsi, kelahiran prematur, IUGR & kematian maternal. Penularan vertikal dari ibu ke janin belum diketahui secara pasti tapi dampak Pandemi Covid-19 terhadap kesehatan maternal di Indonesia dapat terjadi melalui terganggunya pelayanan kesehatan maternal serta risiko infeksi Covid-19 pada ibu hamil. Tujuan penelitian untuk mengetahui Determinan Yang Mempengaruhi Status Kesehatan Ibu Hamil Selama Pandemi Covid-19 Di Praktik Mandiri Bidan Kota Martapura. Desain Penelitian yang digunakan Analitik deskriptif dengan pendekatan cross sectional. Jumlah sampel 100 orang ibu hamil, menggunakan quisioner secara ofline dan online. Analisis yang digunakan uji Korelasi Rank Spearman. Hasil Penelitian menunjukan bahwa ada hubungan yang signifikan antara umur (p 0,001), pendidikan (p 0,037), pengetahuan (p 0,020), Status Ekonomi (p 0,003), Frekuensi ANC(p 0,045), dan riwayat penyakit (p 0,000) dengan Status Kesehatan Ibu Hamil karena nilai p-value < 0,05. Pekerjaan (p 0,816), Paritas (p 0,89), Jarak Kehamilan (p 0,288), dan Status Gizi Ibu Hamil (0,891) memiliki p-value > 0,05 maka secara statistik tidak berhubungan dengan Status Kesehatan Ibu Hamil. Kesimpulan umur, pendidikan, pengetahuan ,Status Ekonomi, Frekuensi ANC dan riwayat penyakit dapat memperngaruhi Status Kesehatan pada Ibu Hamil. Kata Kunci : determinan, status kesehatan ibu hamil, covid-19